1995
DOI: 10.1148/radiology.195.2.7724780
|View full text |Cite
|
Sign up to set email alerts
|

Complications after emergency tube thoracostomy: assessment with CT.

Abstract: Patients undergoing emergency TT are at increased risk for complications. CTM is the most common abnormality and should be diagnosed promptly to prevent additional problems. CT is more useful than plain radiography for establishing a diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(69 citation statements)
references
References 0 publications
2
63
0
4
Order By: Relevance
“…Classifi cation of thoracic drainage system [9,10] Correct position Top of the thoracic drainage lies in the pleural cavity dorsal or ventral to the adjacent parietal pleura …”
Section: Table Imentioning
confidence: 99%
See 1 more Smart Citation
“…Classifi cation of thoracic drainage system [9,10] Correct position Top of the thoracic drainage lies in the pleural cavity dorsal or ventral to the adjacent parietal pleura …”
Section: Table Imentioning
confidence: 99%
“…The main complication here is the misplacement of a drainage. Numerous studies have shown that misplacements of thoracic drainages are accompanied by an increased risk for persistent pneumothorax and hematothorax as well as late complications such as abscesses and empyema [9,20]. Even the possibility of developing a tension pneumothorax through a misplaced drainage is described [21].…”
Section: Access Routementioning
confidence: 99%
“…12). [31][32][33] Malpositioning, especially in the soft tissue of the chest wall, occurs more frequently in obese patients. A malposition should be sus- pected when the drainage function is inadequate or the pneumothorax or pleural effusion persists.…”
Section: Chest Tubesmentioning
confidence: 99%
“…34 CT is, by far, superior to CXR for assessment of drain position and associated complications. 31 Possible complications include bleeding due to laceration of an intercostal vessel, the liver, or the spleen (Fig. 13).…”
Section: Chest Tubesmentioning
confidence: 99%
“…O exame semiológico completo e principalmente a ausculta e percussão torácicas, inspeção da respiração e de turgência jugular, foram a base de sustentação para a decisão do autor, conforme sustenta a literatura, [5][6][7][8][9][10][11][12] para a realização ou não da drenagem pleural naqueles pacientes vítimas de traumatismo fechado ou naqueles em que se suspeitou de pneumotórax espontâneo e que não tinham comprovação radiológica. Todos parâmetros previamente descritos eram reavaliados ao final do atendimento pré-hospitalar no momento da chegada ao pronto socorro hospitalar.…”
Section: Métodounclassified